Baby Boomers and Technology: Factors and Challenges in Utilizing Mobile Devices - (:unkn) unknown (My University, 2015)
This exploratory dissertation study reports an investigation of Baby Boomers utilizing mobile technology to determine how Baby Boomers were utilizing mobile devices and if there were any types of challenges and affecting factors some Baby Boomers could face when searching for information in an online mobile environment. Fifty Baby Boomer participants were recruited by a purposive snowball sampling method and were divided into two groups, twenty-five Younger Boomers and twenty-five Older Boomers to look for comparisons and differences among the Baby Boomers in regards to mobile technology usage, search activities, environmental context, frequency and duration of search activities, as well as the factors and challenges they could encounter while using a mobile device since the age range spans nineteen years. The study was designed to answer two research questions: How are Baby Boomers utilizing a mobile device to search for information in terms of the mobile device types, the environmental contexts and the types of information searched?; and What are the challenges concerning Baby Boomers utilizing a mobile device in searching for information and their affecting factors? This exploratory dissertation study used a qualitative methods approach based in grounded theory to analyze the data. Participants were given a choice of using print or electronic instruments to participate in the study. Multiple collection methods were used to gather the data, consisting of a questionnaire and solicited diaries that were kept for a period of seven days with follow-up interviews given to all participants. The grounded theory approach created a coding schema of ten types of challenges representing five major categories and twenty-three affecting factors. The comparison and interpretation of the search activities, the types of challenges and the affecting factors led to the development of the Baby Boomer Mobile Device Information Searching Model. Theoretical, methodological and practical implications that include system design and library services have been discussed providing suggestions to system designers, researchers and information professionals within and outside the Library and Information Science field.
Keywords: Baby Boomers; Information Retrieval; Information Searching; Mobile Device; Mobile Technology; User-system Interaction